Free Thai personal recollections and official documents - Wimon Wiriyawit (White Lotus Co., Ltd., 1997)
An important eyewitness account of one of the active participants. Group Captain Wimon Wiriyawit is one of the few survivors of a small group of Thais who were in the USA at the beginning of the Pacific War and who volunteered to work for the liberation of Thailand from Japanese occupation. The personal recollections are supported by official documents from US archives, released only recently. This book brings to light the differing agendas of the war allies: the USA, Britain and Nationalist China, as well as different ideas within the Thai political elite.